2011
DOI: 10.2147/eb.s21391
|View full text |Cite
|
Sign up to set email alerts
|

Low-level light therapy of the eye and brain

Abstract: Low-level light therapy (LLLT) using red to near-infrared light energy has gained attention in recent years as a new scientific approach with therapeutic applications in ophthalmology, neurology, and psychiatry. The ongoing therapeutic revolution spearheaded by LLLT is largely propelled by progress in the basic science fields of photobiology and bioenergetics. This paper describes the mechanisms of action of LLLT at the molecular, cellular, and nervous tissue levels. Photoneuromodulation of cytochrome oxidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(70 citation statements)
references
References 100 publications
4
63
0
3
Order By: Relevance
“…Thus, we estimated that about 1.2 J/cm 2 of the 60 J/cm 2 LLLT dose applied reached the surface of the prefrontal cortex. This value is similar to 1 J/cm 2 , the peak effective LLLT dose in neuron cultures for increasing cytochrome oxidase activity (Rojas and Gonzalez-Lima, 2011). …”
Section: Cognitive and Emotional Functionssupporting
confidence: 76%
See 1 more Smart Citation
“…Thus, we estimated that about 1.2 J/cm 2 of the 60 J/cm 2 LLLT dose applied reached the surface of the prefrontal cortex. This value is similar to 1 J/cm 2 , the peak effective LLLT dose in neuron cultures for increasing cytochrome oxidase activity (Rojas and Gonzalez-Lima, 2011). …”
Section: Cognitive and Emotional Functionssupporting
confidence: 76%
“…But for the field of low-level light/laser therapy (LLLT), development of a model of how luminous energy from red-to-near-infrared wavelengths modulates bioenergetics began with in vitro and in vivo discoveries in the last 40 years. Previous LLLT reviews have provided extensive background about historical developments, principles and applications (Rojas and Gonzalez-Lima, 2011, 2013; Chung et al, 2012). The purpose of this paper is to provide an update on LLLT's neurochemical mechanisms supporting transcranial laser stimulation for cognitive-enhancing applications.…”
mentioning
confidence: 99%
“…34 Cerebral blood flow is increased due to the vasodilation that occurs after the release of nitric oxide. 37,39,40 Other studies using various mouse models showed that PBM effectively provided neuroprotection, 41,42 improved memory function, 43 and reduced brain tissue loss. [36][37][38] This mechanism is supported by previously reported animal experiments, which identified increases in cytochrome c oxidase and metabolic capacity following PBM.…”
Section: Photobiomodulation (Pbm) Is a Newly Developed Noninvasivementioning
confidence: 99%
“…Cytochrome c oxidase (COX) in complex IV of the mitochondrial respiration chain has key points of deep red and infrared light absorbance, which can change the redox state of the copper heme in COX (Karu, 2008, Mason et al., 2014, Gonzalez-Lima and Rojas, 2011). Recently, absorbance of one of these wavelengths, 670 nm light, in the retina of aged animals has been shown to improve mitochondrial respiration, increasing their membrane potentials and improve ATP production (Kokkinopoulos et al., 2013, Gkotsi et al., 2014, Calaza et al., 2015).…”
Section: Introductionmentioning
confidence: 99%